To solve the system of equations using the elimination method, we have:
- \(-3x - 4y = -23\) (Equation 1)
- \(3x - 5y = 5\) (Equation 2)
We can eliminate \(x\) by adding Equation 1 and Equation 2 together. First, we can rewrite Equation 1 for elimination:
Multiply Equation 2 by 1 (to keep it unchanged):
(Equation 1) \(-3x - 4y = -23\) (Equation 2) \(3x - 5y = 5\)
Now, add both equations:
\[ (-3x - 4y) + (3x - 5y) = -23 + 5 \]
This results in:
\[ (-4y - 5y) = -18 \] \[ -9y = -18 \]
Now, divide by \(-9\):
\[ y = 2 \]
Now that we have the value of \(y\), we can substitute it back into one of the original equations to find \(x\). Let's use Equation 2:
\[ 3x - 5(2) = 5 \]
This simplifies to:
\[ 3x - 10 = 5 \]
Adding 10 to both sides gives:
\[ 3x = 15 \]
Dividing by 3 yields:
\[ x = 5 \]
Thus, the solution to the system of equations is \((5, 2)\).
The correct response is:
\((5, 2)\)